Together: the rituals, pleasures and politics of cooperation - Sennett, Richard (New Haven, 2012)
"Living with people who differ -racially, ethnically, religiously, or economically- is the most urgent challenge facing civil society today. We tend socially to avoid engaging with people unlike ourselves, and modern politics encourages the politics of the tribe rather than of the city. In this thought-provoking book, Richard Sennett discusses why this has happened and what might be done about it.